Poetic Inquiry as a Research and Engagement Method in Natural Resource Science. Issue 10 (3rd October 2019) - Fernández-Giménez, María E.; Jennings, Louise B.; Wilmer, Hailey
Abstract: Complex and "wicked" natural resource issues often require transdisciplinary research approaches–methods that span boundaries among disciplines and engage multiple sectors of society in the research process. Social-ecological systems approaches acknowledge the complexity of dynamics within and feedbacks between natural and social systems, but have insufficiently incorporated the subjective lived experience, agency, culture and power dynamics of people within these systems. We propose that poetic inquiry, together with poetry-based approaches to engagement and science translation, offers a novel set of methods for data generation, analysis, communication, and engagement for natural resource social scientists. We introduce arts-based research and poetic analysis, their benefits and criteria for quality, and reflect on the transformative potential of poetic inquiry. We present cases of poetic inquiry that disrupted hierarchies and humanized research by centering on the participants' lived experience, evoking emotion, amplifying participants' voices, fostering researcher reflexivity, and encouraging collaborative research and public scholarship.